Interleukin-9 Inhibits Lung Metastasis of Melanoma through Stimulating Anti-Tumor M1 Macrophages - Park, Sang Min (Mol Cells, 2020)
Interleukin-9 (IL-9) is well known for its role in allergic inflammation. For cancer, both pro- and anti-tumor effects of IL-9 were controversially reported, but the impact of IL-9 on tumor metastasis has not yet been clarified. In this study, IL-9 was expressed as a secretory form (sIL-9) and a membrane-bound form (mbIL-9) on B16F10 melanoma cells. The mbIL-9 was engineered as a chimeric protein with the transmembrane and cytoplasmic region of TNF-α. The effect of either mbIL-9 or sIL-9 expressing cells were analyzed on the metastasis capability of the cancer cells. After three weeks of tumor implantation into C57BL/6 mice through the tail vein, the number of tumor modules in lungs injected with IL-9 expressing B16F10 was 5-fold less than that of control groups. The percentages of CD4(+) T cells, CD8(+) T cells, NK cells, and M1 macrophages considerably increased in the lungs of the mice injected with IL-9 expressing cells. Among them, the M1 macrophage subset was the most significantly enhanced. Furthermore, peritoneal macrophages, which were stimulated with either sIL-9 or mbIL-9 expressing transfectant, exerted higher anti-tumor cytotoxicity compared with that of the mock control. The IL-9-stimulated peritoneal macrophages were highly polarized to M1 phenotype. Stimulation of RAW264.7 macrophages with sIL-9 or mbIL-9 expressing cells also significantly increased the cytotoxicity of those macrophages against wild-type B16F10 cells. These results clearly demonstrate that IL-9 can induce an anti-metastasis effect by enhancing the polarization and proliferation of M1 macrophages.